2019
DOI: 10.1002/jcph.1483
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Phase I Metabolism of Drugs

Abstract: Capturing ontogeny of enzymes involved in phase I metabolism is crucial to improve prediction of dose‐concentration and concentration‐effect relationships throughout infancy and childhood. Once captured, these patterns can be integrated in semiphysiologically or physiology‐based pharmacokinetic models to support predictions in specific pediatric settings or to support pediatric drug development. Although these translational efforts are crucial, isoenzyme‐specific ontogeny‐based models should also incorporate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…The ontogenic profile of CES1 has been well established using both immunoblot and proteomic methodologies on large libraries of adult and pediatric liver tissue 39,40 . Overall, the profile is similar to that observed with other phase I drug metabolizing enzymes, where expression is low at birth but quickly rises to approximate adult levels by 2 years of age 41 . Specifically, CES1 expression in neonates is roughly 20% that of adults and reaches 50% of adult levels (i.e., AGE50) by ~ 7 months of age.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The ontogenic profile of CES1 has been well established using both immunoblot and proteomic methodologies on large libraries of adult and pediatric liver tissue 39,40 . Overall, the profile is similar to that observed with other phase I drug metabolizing enzymes, where expression is low at birth but quickly rises to approximate adult levels by 2 years of age 41 . Specifically, CES1 expression in neonates is roughly 20% that of adults and reaches 50% of adult levels (i.e., AGE50) by ~ 7 months of age.…”
Section: Discussionmentioning
confidence: 63%
“…39,40 Overall, the profile is similar to that observed with other phase I drug metabolizing enzymes, where expression is low at birth but quickly rises to approximate adult levels by 2 years of age. 41 Specifically, CES1 expression in neonates is roughly 20% that of adults and reaches 50% of adult levels (i.e., AGE50) by ~ 7 months of age. The exact source for the CES1 ontogenic profile used in SimCYP v.18 was unclear to the authors at the time of this publication, but a very similar profile was observed using proteomic evaluation of N = 171 liver tissue samples and incorporated into a PBPK model for oseltamivir (SimCYP v.15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is a high uncertainty in the maturation pattern of CYP3A4 in this challenging age group , which is further complicated by the potential presence of CYP3A7 enzyme. The latter is absent in adults, but expressed at a high level during foetal life and decreases progressively throughout the first 2 years after birth (Allegaert and van den Anker, 2019). A further study to elucidate CYP3A7 contribution to imatinib metabolism is necessary in order to perform a PBPK prediction with confidence in children less than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The developmental pharmacogenomics (ontogeny + pharmacogenetics) of CYP2C19 in neonates and young infants has been reported with omeprazole as probe drug more recently. At birth, CYP2C19 expression levels are 20-25% of adults and by 1 year of age this has increased to 40-50% [41,42]. This means that the neonate's ability to activate clopidogrel is substantially lower than that of adults.…”
Section: Clopidogrelmentioning
confidence: 99%